1991
DOI: 10.1002/ajmg.1320390203
|View full text |Cite
|
Sign up to set email alerts
|

Mother and son with deletion of 3p25‐pter

Abstract: We report on a mother and son with a 3p25-pter deletion. Both have postnatal growth retardation, mental retardation, apparently low-set or malformed ears, and telecanthus. The mother also has ptosis and multiple joint pains, while the son has a long philtrum and anteverted nares. These phenotypes are compared to those of other 3p- patients. Both patients have many manifestations previously described. The son appears to be more severely affected than the mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…[37][38][39] Remarkably, Knight et al 39 reported a phenotypically normal mother and child both with a terminal 3p25.3 deletion, which suggests that a deletion distal to 3p25.3 does not need to have an apparent deleterious effect.…”
Section: Pmentioning
confidence: 99%
“…[37][38][39] Remarkably, Knight et al 39 reported a phenotypically normal mother and child both with a terminal 3p25.3 deletion, which suggests that a deletion distal to 3p25.3 does not need to have an apparent deleterious effect.…”
Section: Pmentioning
confidence: 99%
“…This rare chromosome disorder has arisen de novo in most reported cases, and is typically a terminal deletion of the short arm of chromosome 3 with breakpoints mapping to chromosome band 3p25 [Verjaal and De Nef, 1978;Garcia Segredo et al, 1981;Witt et al, 1981;Higginbottom et al, 1982;Reifen et al, 1986;Scwyer et al, 1987;Tazelaar et al, 1991;Mowrey et al, 1993;Phipps et al, 1994;Drumheller et al, 1996;Green et al, 2000]. The most common features include low birthweight, growth delay, mental and psychomotor retardation, microcephaly, triangular face, hypotonia, ptosis, hypertelorism, short nose with broad nasal tip, long philtrum, and micrognathia.…”
Section: Introductionmentioning
confidence: 96%
“…A total of 22 cases have been reported and apart from one mother and son pair, all cases have arisen de novo (1)(2)(3)(4)(5). Characteristic features include low birthweight, microcephaly, trigonocephaly, hypotonia, psychomotor and growth retardation, ptosis, telecanthus, downslanting palpebral fissures and micrognathia.…”
Section: Introductionmentioning
confidence: 99%